Application of GenAI in Outcome-Based Education in Teaching Learning Processes - Panda, Snigdharani; Mishra, Pritiprava (Optimality, 2026)
An example of a revolutionary shift in higher education in India is the integration of Generative Artificial Intelligence (GenAI) into the Outcome-Based Education (OBE) framework. National organizations like All India Council for Technology and Education (AICTE), National Board of Accrediation (NBA), and National Assessment and Accrediation Council (NAAC) for accreditation and quality assurance encourage Indian engineering colleges to use learner centred and data-driven methods for learning and continuous improvement of students. Every stage of the educational cycle, from curriculum design to evaluation and documentation, could benefit from the use of GenAI technologies, such as Large Language Models (LLM), content generation systems, and adaptive learning platforms. In addition to providing applications for teaching, assessment, research, and accreditation, the paper addresses at how GenAI technologies complement and enhance the AICTE-NBA-NAAC ecosystem in higher education. This paper is also provides some of the major issues with data integrity, ethical considerations, and faculty awareness and suggests ways to advance responsible AI use in higher education.